2016
DOI: 10.3390/f7040076
|View full text |Cite
|
Sign up to set email alerts
|

Ecofunctional Traits and Biomass Production in Leguminous Tree Species under Fertilization Treatments during Forest Restoration in Amazonia

Abstract: Abstract:Background: Choosing the correct species and fertilization treatments is a determining factor in the success of forest restoration. Methods: A field study was conducted in a degraded area near the Balbina hydroelectric dam in Amazonas State (AM), Brazil, to evaluate two hypotheses: (i) leguminous tree species exhibit differences in growth, leaf nutrient content, and photosynthetic nutrient use efficiencies; and (ii) differences in these characteristics depend on the fertilization treatments to which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“…The relative growth rate of the diameter (RGR D ) of each tree, hereafter the diameter growth, was calculated 24 months after plantating (17). Detailed information on the species used, fertilization methods, experimental trials and monthly precipitation during the experimental period can be found in (25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relative growth rate of the diameter (RGR D ) of each tree, hereafter the diameter growth, was calculated 24 months after plantating (17). Detailed information on the species used, fertilization methods, experimental trials and monthly precipitation during the experimental period can be found in (25).…”
Section: Methodsmentioning
confidence: 99%
“…The P concentration was determined by spectrophotometry at 725 nm. The potassium (K), Ca and Mg, iron (Fe) and zinc (Zn) concentrations were determined using atomic absorption spectrophotometry (PerkinElmer 1100B, Inc., Waltham, MA, USA) according to Jaquetti et al (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Degraded areas in the Amazon Basin with decreased soil organic matter impose multiple nutrient limitations restricting photochemical activities and plant growth [19,20]. Studies have demonstrated the effects of fertilization on biomass growth during forest restoration with leguminous trees [21,22]. Fertilization effects may enhance the drought tolerance of species due to increased quantum yield [23,24].…”
Section: Introductionmentioning
confidence: 99%